Potential benefit of lamotrigine in managing ketamine use disorder. (February 2016) - Huang, Ming-Chyi; Chen, Lian-Yu; Chen, Chih-Ken; Lin, Shih-Ku
Abstract: Ketamine is an anesthetic derivative of phencyclidine (PCP; 'Angel dust') with dissociative, analgesic and psychedelic properties. Ketamine has become a popular recreational drug of abuse in many parts of the world in recent years. The preclinical studies demonstrate the reinforcing effects of ketamine and long-term ketamine abuse induces a delayed and persistent upregulation of dopamine system. In humans, there have been concerns about its liability to development of addiction. The dilemma of mental professionals in managing the treatment-seeking ketamine abusers comes from a lack of effective pharmacotherapy. Limiting evidence showed that lamotrigine, which inhibits glutamate release, is effective to reduce cocaine craving. We propose that lamotrigine might be beneficial for managing ketamine use disorder clinically. We also reported one case of ketamine use disorder who experienced a great reduction in craving and ketamine use after taking lamotrigine. Although the mechanisms underlying neuroadaptation and reward related to ketamine are not entirely clear, future clinical trials are needed to advance our understanding of the benefit yielded by lamotrigine to treat ketamine use disorder.